Serendipitous Supernormality - Behzad B. Pavri; Eitan Frankel (Annals of Noninvasive Electrocardiology)
ABSTRACT We describe a patient who underwent AV node modification to create complete heart block in the setting of incessant, ablation‐and‐drug‐refractory, symptomatic atypical atrial flutter. His dual chamber defibrillator (previously implanted for resuscitated cardiac arrest) was programmed to the VVIR mode at a faster pacing rate of 85 bpm. Serendipitously, this rate was an almost exact factorial of his flutter rate of 250–260 bpm. This resulted in every 6th flutter wave falling in the supernormal period, resulting in fixed‐coupled supraventricular bigeminy and trigeminy in the setting of complete heart block. Reprogramming the pacing rate to 75 bpm abolished bigeminy and trigeminy.